Invisible and Precarious: A Scoping Review of Gender-based Violence in Agricultural Streams of Canada’s Temporary Foreign Worker Program - Sarapura, Silvia; Potter, Charlotte; Zink, Regan; Fontecha, Margarita; Cupolo, Nicole (University of Guelph, 2023)
Canada’s agricultural sector relies heavily on labor from temporary foreign agricultural workers (TFAWs). However, TFAWs experience complex vulnerabilities resulting from structural inequalities and discrimination within Canada’s Temporary Foreign Worker Program (TFWP). Multiple, diverse, intersecting social identities of TFAWs (e.g., gender, age, race, nationality, etc.) compound, making TFAWs more or less vulnerable to gender-based violence (GBV) and discrimination in Canada and at home. This scoping review contributes to conceptual and practical knowledge regarding GBV in Canada’s agricultural TFWP. This research was guided by four objectives: (1) collect documented evidence regarding GBV and TFAWs in the agricultural sector, (2) describe how GBV is experienced differently by diverse groups of TFAWs in Ontario, Quebec and British Columbia, (3) understand how policies address or confront GBV experienced by TFAWs in these three provinces, and (4) outline existing infrastructure that supports TFAWs and how supports can be enhanced to better support TFAWs who experience GBV. Using a gender-transformative approach informed by systems thinking and intersectionality, this study examined how structures and institutions (formal and informal) create and exacerbate inequalities between TFAW. This study found that literature on TFAWs in Canada is genderblind, with limited discussion or reporting on GBV within the program. National and transnational policies impacting the TFWP establish and maintain structural vulnerabilities and power imbalances, making TFAWs less likely to report grievances. If workers are to be adequately protected, holistic, cohesive, and diversified support mechanisms are needed to support TFAWs’ access to rights, services, and protections against GBV in Canada.